Studies on calcium carbonate loaded liquid core capsules as a pH controller in lactic acid fermentation - Nurul Ainina Zulkifli (School of Bioprocess Engineering, Universiti Malaysia Perlis, 2014)
Liquid-core capsule composed of calcium carbonate (CaCO3) and carboxyl methyl cellulose (CMC) as inner liquid-core surrounded by a cross-linked alginate membrane was prepared in this study. Liquid-core capsules have been widely used in various industrial applications.